2018
DOI: 10.1017/s0954579418000627
|View full text |Cite
|
Sign up to set email alerts
|

The early care environment and DNA methylome variation in childhood

Abstract: Prenatal adversity shapes child neurodevelopment and risk for later mental health problems. The quality of the early care environment can buffer some of the negative effects of prenatal adversity on child development. Retrospective studies, in adult samples, highlight epigenetic modifications as sentinel markers of the quality of the early care environment; however, comparable data from pediatric cohorts are lacking. Participants were drawn from the Maternal Adversity Vulnerability and Neurodevelopment (MAVAN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 84 publications
(112 reference statements)
5
42
0
Order By: Relevance
“…Eight studies analyzed how maternal behavior can be a predictor of a certain outcome . The remaining three assessed the role of maternal behavior in interaction with early adversities and/or epigenetic regulation .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight studies analyzed how maternal behavior can be a predictor of a certain outcome . The remaining three assessed the role of maternal behavior in interaction with early adversities and/or epigenetic regulation .…”
Section: Resultsmentioning
confidence: 99%
“…A summary of each study timeline is reported in Figure . Five papers had a prospective study design while the other six had a retrospective study design. Adult studies were included only if they retrospectively investigated the link between adversity in infancy or childhood and epigenetic markers later in life.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations